Prevalence and correlates of ADHD among adolescents in a Beirut community sample: results from the BEI-PSY Study - Elias Ghossoub; Lilian A. Ghandour; Fadi Halabi; Pia Zeinoun; Al Amira Safa Shehab; Fadi T. Maalouf (BMC, 2017)
Abstract Background This study aims to investigate the prevalence, correlates and treatment seeking behavior related to ADHD among adolescents from Lebanon. Methods Five hundred and ten adolescents were recruited through multistage stratified cluster sampling of households in Beirut, and separately interviewed along with one parent/legal guardian, using the DAWBA. All adolescents completed the PRQ and the SDQ; the parent/legal guardian also completed the SDQ and provided basic demographic information, including attitudes towards seeking mental health services. Results 10.20% of the adolescents were diagnosed with ADHD. Having ADHD was associated with having academic difficulties and being involved in bullying. Adolescents with ADHD also had higher odds of drinking alcohol, smoking cigarettes, and having comorbid emotional and conduct disorders (compared to those without ADHD). Adolescents with ADHD and their parents reported a higher burden of illness and were more likely to consider seeing a mental health professional than healthy adolescents and their parents. Conclusion ADHD among adolescents in Lebanon warrants closer attention, mainly increased awareness in the larger public, and stronger commitment to increase treatment resources to the community.